Production of prostaglandins, isoprostanes and thromboxane by Aspergillus fumigatus: Identification by gas chromatography-tandem mass spectrometry and quantification by enzyme immunoassay - Kupfahl, Claudio; Geginat, Gernot; Hof, Herbert (Molecular immunology, 2012)
Aspergillus fumigatus has been reported to produce prostaglandin (PG)-like substances. The molecular structure of these fungal eicosanoids is however still unknown. By using the gas chromatography-tandem mass spectrometry (GC-MS/MS) methodology we identified a number of eicosanoids that were formed upon incubation of the precursor arachidonic acid ethyl ester (AAE, 10μM) with three strains of A. fumigatus. The eicosanoids identified include the prostaglandins (PG) PGE2, 6-keto-PGF1α (the stable hydrolysis product of prostacyclin PGI2) and PGF2α, the isoprostanes 15(S)-8-iso-PGF2α and 15(S)-8-iso-PGE2, and thromboxane B2 (TxB2, the stable hydrolysis product of TxA2). These eicosanoids are identical with those produced by cyclooxygenases (COX) in humans. The biosynthesis of all of these eicosanoids could not be inhibited by the human COX inhibitors indomethacin (100μM), acetylsalicylic acid (100μM) or the non-selective human lipoxygenase (LOX) inhibitor nordihydroguaiaretic acid (100μM). By contrast, the selen-containing antioxidant ebselen (100μM) was found to inhibit their synthesis. Our results suggest that mammals and fungi employ different eicosanoid biosynthesis pathways. As some of the detected eicosanoids are potent immunomodulators and bronchoconstrictors, they could play a possible role in pulmonary diseases associated with A. fumigatus infection.